African Quest for Development and Chinese Strategic Policy in the Continent: Myth or Reality in a Developmental Path in the 21st Century - Ojakorotu, Victor; Dan-Woniowei, Fie David (Journal of Reviews on Global Economics, 2019)
Bilateral or multilateral relationships among nations or regional blocs are changing rapidly. For instance, Chinese interest in Africa, which began since the early part of the 21st Century, have assumed incredible dimensions. Since then, the growing Chinese footprints in Africa have orchestrated various debates within the academia and public policy experts, describing their relationship as a â€œmajor geopolitical featureâ€ in this era of a globalised world. A situation that calls for understanding of the nature of their relationship with a view of creating an integrated African policy framework to tackle perceived negative trends of Chinese role in the Continent vis-Ã -vis the developmental challenges of African States. Such views have been quite diverse and contentious over the years. Quite a number of views suggests that China's new relationship with the Continent is a substitute to Western relationship that can offer the needed partnership for the most needed economic growth and infrastructural development of African States. This position informed the initiative called the Forum on China-Africa Cooperation (FOCAC) in the year 2000, and its subsequent formation in 2010 with the ultimate objective of implementing both political and economic programmes in Africa (Stahl, 2016). Available records show that China have implemented two coherent policies on Africa between 2006 and 2015. Against this backdrop, came the warnings of some scholars as well as States to African States to be wary of such Chinese benevolence. The West championed by Washington and Brussels were among such active voices. From the two extreme viewpoints, lies the desire of this paper to analyse holistically, Chinese strategic policy outcomes vis-Ã -vis the African development needs from 2014 to date. The intention is to contribute to the ongoing debate about Africa-China relations vis-Ã -vis the development needs of the Continent. Such holistic analytical approach will further expose the potential impact of the Chinese strategic policy outcomes and the extent of development of African States. Interestingly, the paper will be able to throw open to African States of the choice to doing business with whomever they like based on their development challenges or needs per time and not because of colonial ties or linkages.